2016
DOI: 10.5009/gnl14381
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal Squamous Cell Carcinoma Patients Have an Increased Risk of Coexisting Colorectal Neoplasms

Abstract: Background/AimsEsophageal squamous cell carcinoma (ESCC) and colorectal neoplasms (CRNs) share risk factors. We aimed to investigate whether the CRN risk is increased in ESCC patients.MethodsESCC patients who underwent a colonoscopy within 1 year of diagnosis were retrospectively analyzed. Patients were matched 1:3 by age, gender, and body mass index to asymptomatic controls. CRN was defined as the histological confirmation of adenoma or adenocarcinoma. Advanced CRN was defined as any of the following: ≥3 aden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…The results of this study were consistent with some other studies that reported the significant association between opium consumption with gastrointestinal tract cancers, especially with upper gastrointestinal cancers such as esophagus and gastric cancer (24,34). Also, some studies reported that the risk of colorectal cancer is high in patients with esophageal cancer (35). The common risk factors for colorectal and esophageal cancer may play an important role in this comorbidity, so the findings of this study show that opium consumption relatively increases the risk of colorectal cancers as much as esophageal cancer in opium users.…”
Section: Discussionsupporting
confidence: 82%
“…The results of this study were consistent with some other studies that reported the significant association between opium consumption with gastrointestinal tract cancers, especially with upper gastrointestinal cancers such as esophagus and gastric cancer (24,34). Also, some studies reported that the risk of colorectal cancer is high in patients with esophageal cancer (35). The common risk factors for colorectal and esophageal cancer may play an important role in this comorbidity, so the findings of this study show that opium consumption relatively increases the risk of colorectal cancers as much as esophageal cancer in opium users.…”
Section: Discussionsupporting
confidence: 82%
“…Other studies showed that colorectal cancers comprise up to 16% of esophageal secondary primary malignancies. 9 However, no previous studies reported isolated EAC metastasis to the colon. There is a reported case of EAC metastasis to the colon, liver, and para-aortic lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…Superficial ESCC before and after therapy is known to often coincide with primary cancers at other sites, notably the head and neck, stomach, and lung [ 5 , 6 , 10 , 11 ]. The association of CRN has mostly been described with advanced stage ESCC, and even though the proportion of advanced CRN varies widely with reported extremes of 7-66.7%, its frequency is undoubtedly high [ 12 , 13 ]. However, no reports are available concerning CRN in superficial ESCC limited to cases treated with ER, which prompted us to investigate whether similar to the early stage of esophageal cancer the frequency of CRN would be equally high.…”
Section: Discussionmentioning
confidence: 99%
“…Sites of second and third primary cancers developing in these patients include head/neck, stomach, and lung [ 4 - 6 ], while in recent years, colorectal neoplasm (CRN) also frequents coexists [ 10 - 13 ], and thus colonoscopy is recommended in this patient group. In particular, Baeg et al [ 12 ] have argued that since CRN is frequently detected both before and after therapy for ESCC, colonoscopy should be considered when ESCC is first diagnosed. However, these reports focused on esophageal adenocarcinoma [ 10 ], and, even when addressing ESCC, they concentrated on advanced tumors [ 11 , 13 ] with much less attention devoted to the frequency of CRN coexisting with superficial ESCC or the need for colonoscopy in this context.…”
Section: Introductionmentioning
confidence: 99%